(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Herbal medicine is currently enjoying a revival in popularity in the west and in many parts of theworld. Now a day, various herbal formulations phyotoformulations are commercially available for theprevention and treatment of hepatotoxicity. Taraxacum officinale (dandelion) contains compounds withvarious medicinal activities. This dissertation work was an attempt to establish scientific protocols toperform pharmacological investigation research on Taraxacum officinale for anti-hepatoxic effect againstparacetamol. High amount of total phenolics and total flavonoid content were found in the EETOL Extractthan EETOR Extract.In toxicity studies, mortality rates were zero percent and dandelion extracts possess wide safety marginand classified as Non-Toxic Constituent. Extracts caused slight change blood parameters whereas LFTswere not significantly altered. In anti-hepatotoxic pharmacological studies, PCM induced hepatoxicity byglutathione depletion, necrosis of hepatocytes, elevated levels LFTs with centilobular necrosis. EETOLextract produced remarkable anti-hepatotoxic activity with significant alleviation of LFTs and reddishcoloration, normal anatomical architecture of the hepatocytes (reversal effects). Anti-hepatotoxic effectswere comparatively lesser then standard Silymarin and pharmacodynamics includes membranestabilization inhibition of phopholipase A2 anti-inflammatory anti-oxidant attenuation of depletion ofglutathione and enhanced proteins synthesis. Further, in thiopentone sodium induced sleeping timeanalysis, reduction in sleeping time was recorded in dandelion EETOL extract treated animals whencompared to toxic control animals.